Role of the vitamin C in diethylnitrosamine-induced esophageal cancer in Wistar rats - Ramos,Almino Cardoso (2009)
PURPOSE: To evaluate the inhibitory effect of vitamin C on the experimental esophageal carcinogenesis induced by diethylnitrosamine (NDEA). METHODS: Sixty Wistar male rats aged three months, with mean weight of 210 g were employed in the study and were divided into four different groups according to the drinking drugs: group I - controls: only water, seven days a week; group II - only vitamin C, seven days a week; group III - NDEA, three days a week and water during the other four days; group IV - NDEA, three days a week and vitamin C during the other four days; group V - NDEA together with vitamin C three days a week, and only water during the other four days and group VI - NDEA together with vitamin C three days a week and vitamin C during the other four days. The dosages of NDEA were: - 10 mg. / Kg / day and vitamin C - 200 mg / animal / day, dissolved in drinking water. The animals were observed during 180 days and after that each one was sacrificed and its esophagus and the stomach were removed together and macro and microscopically analyzed to identify any tumors. RESULTS: The largest number of tumors was observed in the group III: 48 macroscopic lesions (4.8 lesions per animal) and 23 microscopic lesions (2.3 lesions per animal). The groups that received vitamin C (groups IV, V and VI) showed smaller number of tumors: group V - 0.5 macroscopic lesions and 0.3 microscopic lesions per animal and group VI - 0.1 macroscopic lesions and 0.1 microscopic lesions per animal. The incidence of tumors in the groups V and VI showed statistical significance (p<0.05), when compared to the other groups. CONCLUSION: The vitamin C administered together with diethylnitrosamine showed an inhibitory effect on the experimental esophageal carcinogenesis in Wistar rats.